The L(2,1) Labeling of Windmill, Binomial Tree, Pan, Gear, Prism, Helm, Lilly, Hurdle, and Key Graph - Lisa Damayanti Ningrum; Noval Putra Ramadhani; Fidelis Nofertinus Zai (Talenta Publisher, 2025)
Let be a graph. Let whole number-valued function such that, and are two adjacent vertices in then if and if The function is called labeling. The labeling number of , called is the smallest number for label of . In this research, we will further discuss the labeling of windmill, binomial tree, pan, gear, prism, helm, lilly, hurdle, and key graph.